Quality Control of Dry Noodle Product Processing in Semarang Central Java - Safitri, Rosdiana Dewi; Khairi, Amalya Nurul (Journal of Agri-Food Science and Technology, 2021)
Quality control is needed to produce quality products. Quality control is aimed at reducing defects in production results. In this study, we focus on the analysis of the types of defects, the number of defects, and the causes of defects in dry noodles, including the attributes of moisture content, shape, and packaging. The population in data collection was all dry noodle. The sampling method for the moisture content attribute was purposive sampling. Data collection methods by observation, interview, and literature study. Data were analyzed using pareto chart, control chart (p-chart), and fishbone diagram. The control chart showed four points of defective products that were beyond the control limits and six points that were within the control limits. Finally, the fishbone diagram demonstrated that two dominant factors causing defects in dry noodle products were machine and the processing method.